Energy saving glass: modelling the coating design from mathematical perspective - Abal Abas, Zuraida; Shaffiei, Zatul Amilah; Zainal Abidin, Zaheera; Abdul Rahman, Ahmad Fadzli Nizam; Jasmi, Muhammad Izzuddin (Taylor's University, 2019)
Buildings are recently equipped with special coated energy saving glass as window. The function of this glass is to be the outer shell that protects us from the exposure of dangerous Ultra-violet rays, direct sunlight and heat. The glass is also able to maintain the internal temperature at a suitable condition in the building. The invention of this energy saving with extensive technology of lowemissivity glass is very significant in our daily lives, which can help in reducing the electricity usage. However, the glass attenuates communication signals such as global positioning system, mobile phone and wireless broadband; due to the fabricated coating layer on the window. Therefore, this paper aims to propose a new mathematical model of optimum coating design for the energy saving glass. It uses Harmony search to obtain the optimum result. The model starts by manipulating the plate design into desired grid and fill in the grid with binary number based on the mathematical model. The optimum binary result is then converted into coating shape design for energy saving glass in the Computer Simulation Technology Studio. The performance of transmission coefficient and return loss is used to evaluate the resulted shape design structure in which, the resulted efficiency is 99.88%.